Iris Murdoch, A Writer at War : Letters and Diaries, 1939-1945. - Conradi, Peter J. (Oxford University Press, USA, 2011)
These never before published writings comprise Iris Murdoch's passionate wartime correspondence with two early intimates: the poet Frank Thompson, brother of the historian E.P. Thompson, who was killed in 1944, and David Hicks, with whom she had a dramatic affair, engagement, and breakup. It also includes the journal that Murdoch kept as a touring actress during August of 1939. The selection sheds new light on a brilliant young mind ("sharp and polished as a sword" as Frances Wilson describes it), while painting a vivid picture of life during the Second World War.